Aggressive, multifocal oral verrucous leukoplakia: proliferative verrucous leukoplakia or not? - Ghazali, N.; Bakri, M.M.; Zain, R.B. (Wiley, 2003)
Background: Some oral verrucal lesions may constitute parts of the clinicopathological spectrum of proliferative verrucous leukoplakia (PVL). Because of its idiopathic yet sinister nature, it is possible that PVL may exist in other populations. The aim of this study was to review the clinicopathological features of persistent, multifocal, oral verrucal lesions in Malaysian population. Methods: Patients with multifocal oral verrucal lesions were selected from surgical and histopathological records. Results: Nine patients of diverse ethnicity with 43 biopsies were reviewed. The mean age at the presentation was 62 years. The most frequent sites affected were gum, sulci, cheek and tongue. Indulgence in risk habits was reported in about 70 of patients. Four cases developed multifocal carcinoma from multifocal leukoplakia. Conclusions: In retrospect, none of the cases fulfilled the original PVL criteria, although three cases were suggestive of PVL. Nevertheless, these findings do not necessarily preclude the existence of PVL as a clinicopathological entity in Malaysian population.